Alkaline ceramidase (ClAC) inhibition enhances heat stress response in Cyrtorhinus lividipennis (Reuter) - Chen, Min; Shi, Xiao-Xiao; Wang, Ni; Zhang, Chao; Shi, Zhe-Yi; Zhou, Wen-Wu; Zhu, Zeng-Rong (Frontiers in Physiology, 2023)
Ceramidases (CDase) are vital sphingolipid enzymes involved in organismal growth and development. They have been reported as key mediators of thermal stress response. However, whether and how CDase responds to heat stress in insects remains unclear. Herein, we identified two CDase genes, C. lividipennis alkaline ceramidase (ClAC) and neutral ceramidase (ClNC), by searching the transcriptome and genome databases of the mirid bug, Cyrtorhinus lividipennis, an important natural predator of planthoppers. Quantitative PCR (qPCR) analysis showed that both ClNC and ClAC were higher expressed in nymphs than in adults. The ClAC was especially highly expressed in the head, thorax, and legs, while ClNC was widely expressed in the tested organs. Only the ClAC transcription was significantly affected by heat stress. Knocking down ClAC increased the C. lividipennis nymph survival rate under heat stress. The transcriptome and lipidomics data showed that the RNA interference-mediated suppression of ClAC significantly upregulated the transcription level of catalase (CAT) and the content of long-chain base ceramides, including C16-, C18-, C24- and C31- ceramides. In C. lividipennis nymphs, ClAC played an important role in heat stress response, and the upregulation of nymph survival rate might be caused by variation in the ceramide levels and transcriptional changes in CDase downstream genes. This study improves our understanding of the physiological functions of insect CDase under heat stress and provides valuable insights into the nature enemy application.